2014
DOI: 10.1088/0004-637x/791/2/113
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Infrared-Selected Quasars. I. Virial Black Hole Mass and Eddington Ratios

Abstract: We provide a catalog of 391 mid-infrared-selected (MIR; 24 μm) broad-emission-line (BEL; type 1) quasars in the 22 deg 2 SWIRE Lockman Hole field. This quasar sample is selected in the MIR from Spitzer MIPS with S 24 > 400 μJy, jointly with an optical magnitude limit of r (AB) < 22.5 for broad line identification. The catalog is based on MMT and Sloan Digital Sky Survey (SDSS) spectroscopy to select BEL quasars, extending the SDSS coverage to fainter magnitudes and lower redshifts, and recovers a more complete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 121 publications
(213 reference statements)
2
16
0
Order By: Relevance
“…The selection criteria in X15 is comparable to our sample as both require detections in X-ray and FIR, except that X15 has an additional selection based on MIPS 24µ m flux. The 24µ m flux selection is highly complete for AGNs (Krawczyk et al 2013;Dai et al 2014), which is again confirmed by the similar fitting results.…”
Section: Correlation Between Agn Activity and Star Formationsupporting
confidence: 81%
See 3 more Smart Citations
“…The selection criteria in X15 is comparable to our sample as both require detections in X-ray and FIR, except that X15 has an additional selection based on MIPS 24µ m flux. The 24µ m flux selection is highly complete for AGNs (Krawczyk et al 2013;Dai et al 2014), which is again confirmed by the similar fitting results.…”
Section: Correlation Between Agn Activity and Star Formationsupporting
confidence: 81%
“…On the other hand, SMBH mass is well-known to decrease to-wards lower redshift in optical type 1 AGNs (e.g. Labita et al 2009;Dai et al 2014). The mass downsizing effect would result in higher L AGN at high z, as demonstrated earlier in Figure. 2.…”
Section: Correlation Between Agn Activity and Star Formationmentioning
confidence: 72%
See 2 more Smart Citations
“…Such obscured ("type 2") active galactic nuclei (AGNs) can be identified from narrow optical emission lines (Zakamska et al 2003(Zakamska et al , 2004(Zakamska et al , 2005Reyes et al 2008;Yuan et al 2016), radio luminosity (e.g., McCarthy 1993Martínez-Sansigre et al 2006;Seymour et al 2007;Wilkes et al 2013), or X-ray properties (e.g Alexander et al 2001;Stern et al 2002;Treister et al 2004;Vignali et al 2006Vignali et al , 2009Del Moro et al 2014). In addition, pioneering work with the Spitzer Space Telescope demonstrated that obscured quasars have similar mid-infrared (MIR) SEDs to their unobscured counterparts but are dominated by host galaxy light in the optical (Lacy et al 2004;Rowan-Robinson et al 2005;Stern et al 2005;Alonso-Herrero et al 2006;Martínez-Sansigre et al 2006;Polletta et al 2006;Hickox et al 2007;Donley et al 2008;Lacy et al 2013Lacy et al , 2015Dai et al 2014). Consequently, obscured quasars can be most efficiently selected in the MIR, as they appear very red in the IRAC [3.6] -[4.5] color, characteristic of the "hot" MIR SED that is evident in broadline quasars (e.g., Richards et al 2006;Assef et al 2010, hereafter R06 and A10, respectively).…”
Section: Introductionmentioning
confidence: 99%